Analisis Kemampuan Numerasi Peserta Didik Kelas 1 Madrasah Ibtidaiyah Berdasarkan Level Kognitif - Zulfa Zachri Wahyudi; Nurdiana Siregar; Rora Rizky Wandini (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to identify the numeracy ability of grade I students of Madrasah Ibtidaiyah Based on Cognitive Level. The research method used is quantitative with a descriptive approach. The population used by all students of MIN 4 Medan. Sampling from the population used the Issac Michael technique which obtained a result of 249 from the entire population. Furthermore, samples were taken using cluster sampling which was specifically for classes I, A and I B, a total of 56. The test instrument is in the form of an objective description of the